Identifikasi Performa Produksi dan Service Periode Sapi Pesisir dan Hasil Persilangan Inseminasi Buatan Di Kabupaten Pesisir Selatan Sumatera Barat - Sulin, Irwandi (Jurnal Embrio, 2008)
Performance of cattle production and reproduction is one of the indicator to determine the ability of cattle production by estimate the weigh and the body size into group of age and the criteria of group of age and criteria of group cattle.beside to prepare the production management and reproduction where one of them wel to use in a process of cattle production from now and then. In this research can find that the performance of weigh production into local cow after weaning ( 8 month – 1 year ) is 114,49 kg and crossing IB Pesisir 157087 kg. the weigh according to age class in various of weigh-in show that the indication of weigh differentiate among local heifer to crossing IB of local cow about 90%.The crossing IB gives the production ressult well then local cow. Compared to saladdin’s research (1983) the weigh of local cow decrease from 1982 to 2004.During 22 years has decreased the weigh of bull and cow in the equal comparison from 1982 to 2004 about 35.07%.The analyze of body size into kind sex show that distinguish of size composition between local cow to crossing IB,either in the mature of cow or the bull. In the analyze of service Preconception (SC) in caring management of local cow with crossing IB find that the significant differention,where SC of local cow gets 12,8 month and crossing IB cow only 3.333 months.it’s very determined by caring management factor of pople and local animal husbandary department.